Study of Navier-Stokes equation by using Iterative Laplace Transform Method (ILTM) involving Caputo- Fabrizio fractional operator. (December 2020) - Yadav, Lokesh Kumar; Agarwal, Garima; Kumari, Manjeet
Abstract: This article arrangement with N-S equation containing the Caputo-Fabrizio differential operator of fractional order. The Iterative Laplace Transform Method (ILTM) has been applied to found numerical solution of time-fractional N-S equation in a tube with unsteady fluid flow in the Caputo-Fabrizio sense. The ILTM is an elegant coupling of transform of the Laplace and new Iterative method (NIM). This scheme provides numerical solution in the terms of power series with easily computable terms. It is observed that the solutions of N-S equations obtained by the ILTM rapidly convergent to exact solutions.